Functional Analysis of the Engineered Cardiac Tissue Grown on Recombinant Spidroin Fiber Meshes - Teplenin, Alexander; Krasheninnikova, Anna; Agladze, Nadezhda; Sidoruk, Konstantin; Agapova, Olga; Agapov, Igor; Bogush, Vladimir; Agladze, Konstantin (PLOS ONE, 2015)
In the present study, we examined the ability of the recombinant spidroin to serve as a substrate for the cardiac tissue engineering. For this purpose, isolated neonatal rat cardiomyocytes were seeded on the electrospun spidroin fiber matrices and cultured to form the confluent cardiac monolayers. Besides the adhesion assay and immunostaining analysis, we tested the ability of the cultured cardiomyocytes to form a functional cardiac syncytium by studying excitation propagation in the cultured tissue with the aid of optical mapping. It was demonstrated that recombinant spidroin fiber meshes are directly suitable for the adherence and growth of the cardiomyocytes without additional coating with the attachment factors, such as fibronectin.